The Relationship Between Blue Accounting, Marine Policy and Climate Change To The Sustainability Of Marine Ecosystems - Larasasti, Sindy; Putri Nazwa Amalia; Icha Santika; Annisa Putri; Febyola Crisanta; Vina Arnita (Journal of Environmental Economics and Sustainability, 2025)
Indonesia is the world’s largest archipelago, rich in marine resources. However, the management of these resources faces a number of challenges, including overexploitation, climate change and uncoordinated policies. This research aims to assess how blue accounting, marine policy and climate change affect the sustainability of marine ecosystems. Blue accounting is a strategy for measuring the economic, social and environmental value of marine ecosystems. It supports environmentally sound business practices and increases transparency in the management of marine resources. Marine policies, such as the World Maritime Axis vision and PIT, aim to ensure the sustainable use of the oceans. However, overlapping regulations, resource exploitation and climate change impacts such as extreme weather events and sea level rise are degrading marine ecosystems and threatening coastal communities. This research uses a descriptive qualitative method with a literature review approach to explore the relationship between these three factors. The results show that the implementation of blue accounting and appropriate marine policies, coupled with climate change mitigation, can maintain the sustainability of marine ecosystems and support sustainable economic development.